Asset bubble detection, causation and responses in a period of expansionary monetary policy - Garry, Sebastian (2021)
This study investigates if there are asset bubbles present in the stock, housing and bond markets of the US, and explores the influence the Fed has had on asset prices through expansionary monetary policy. By utilising the GSADF procedure, a new bubble monitoring econometric process developed by Phillips et al (2015), I was able to find evidence of explosive prices in current house prices suggesting the presence of a bubble. Stocks and bonds did not present evidence of explosive prices, but the absolute values of fundamental ratios imply possible risk mispricing. The Federal Reserve’s quantitative easing and low funds rate have led to justifiable increases in asset pricing, but possible excess market liquidity could be contributing to prices deviating from fundamental value across asset classes. A ‘lean against’ bubble policy of slight monetary tightening or signalling is advised but high levels of corporate and public debt make the US very interest rate sensitive, leaving the Fed to tread a very narrow path, navigating through CPI and asset price inflation.